The political economy of China-U.S. relations: the group of two - Lairson, Thomas D. (Henry Stewart Talks, 2013)
Complex interdependence, Deep interdependence, Multiple forms of interdependence, Differentiated gains and loses, Management of interdependence, Foreign direct investment, Foreign invested enterprises, Regional production networks, Trade imbalances, Foreign reserve holdings, Economic rebalancing, Beijing Consensus, Washington Consensus, Preferential trade agreements, ASEAN, Trans-Pacific Partnership, Exchange rate conflict, Liberalization of exchange rate, Financial power, Consumption, Investment, Urbanization, Transnational firm strategies, Competitiveness, Innovation, Clean energy competition, Shifting balance of political-economic power